1991
DOI: 10.1111/j.1744-7348.1991.tb04845.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rotation length, fungicide treatment of seed tubers and nematicide on diseases and the quality of potato tubers

Abstract: SummaryIn 1982 – 88, potatoes were grown in 2‐, 4‐ and 6‐course rotations with spring barley on a field infested with Globodera rostochiensis. Severity of stem canker and black scurf increased with increasing frequency of previous potato crops, and seed tuber treatment with tolclofos‐methyl became less effective in controlling diseases. This suggested that previous crops had increased the amounts of soil‐borne inoculum of Rhizoctonia solani. Oxamyl soil treatment increased stem canker in one year and decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 8 publications
1
31
0
Order By: Relevance
“…Although H. solani is a pathogen of tuber-bearing Solanum species only (Rodriguez et al 1995), saprophytic colonization of senescing alfalfa, sorghum, rye, oats, corn, wheat, rapeseed, red clover, and buckwheat was also observed, suggesting a mechanism for overwinter survival (Mérida and Loria 1994). Based on the apparent presence of soil-borne inoculum, crop rotation has been suggested as a management tool for control of silver scurf (Hide and Read 1991;Secor and Gudmestad 1999).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although H. solani is a pathogen of tuber-bearing Solanum species only (Rodriguez et al 1995), saprophytic colonization of senescing alfalfa, sorghum, rye, oats, corn, wheat, rapeseed, red clover, and buckwheat was also observed, suggesting a mechanism for overwinter survival (Mérida and Loria 1994). Based on the apparent presence of soil-borne inoculum, crop rotation has been suggested as a management tool for control of silver scurf (Hide and Read 1991;Secor and Gudmestad 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Crop rotation has often provided little benefit for control of common scab (Scholte 1990;Hide and Read 1991), since the ability of pathogenic Streptomyces spp. to survive in soil or on plant residues for over a decade can circumvent any short term rotation benefits (Kritzman and Grinstein 1991).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, our results indicated that soil inoculum only occasionally played a significant role in stem and stolon disease incidence. Previous studies have shown that disease incidence increases with increasing soil inoculum level and potato cropping frequency (Banville 1989;Hide and Read 1991;Gilligan et al 1996). Gilligan et al (1996) showed that when following a susceptible rotation crop 70% to 80% of potato plants could become infected from soil-borne inoculum.…”
Section: Discussionmentioning
confidence: 98%
“…This has led to epidemics of many plant diseases including those caused by Rhizoctonia solani (Hide and Read, 1991;Huiskamp and Lamers, 1992). On the other hand, decline in Rhizoctonia diseases also has been observed with mono-culture in raddish (Wijetunga and Baker, 1979) and potatoes (Jager and Velvis, 1980).…”
Section: Crop Rotationmentioning
confidence: 99%